Niobium-nitrides derived from nitrogen splitting1. Issue 17 (28th February 2015) - Searles, Keith; Carroll, Patrick J.; Chen, Chun-Hsing; Pink, Maren; Mindiola, Daniel J.
<x xml:space="preserve">Abstract</x> Under reducing conditions the complex [(ArO)2Nb(μ-Cl)Cl2]2 undergoes a series of color changes which ultimately result in the splitting of atmospheric N2 to form nitride species. Nb(iv) and Nb(iii) species produced in this interesting transformation have been isolated and the possibility of a Nb(ii) species being responsible in the N2 activation and splitting process is discussed.